2008
DOI: 10.1177/1087054707305168
|View full text |Cite
|
Sign up to set email alerts
|

Injury Among Stimulant-Treated Youth With ADHD

Abstract: These findings reveal several patient characteristics that may be associated with increased risk of injury among children and adolescents treated for ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 30 publications
4
41
0
1
Order By: Relevance
“…In a second study, Marcus et al assessed injury risk among stimulant-treated children over a single treatment period of at least 4 months. Children who were more adherent to medication were less likely to experience an injury than children who were less adherent (injuries/person-year: 0.227; 95% CI 0.214 to 0.240 vs 0.230; 95% CI 0.204 to 0.254; adjusted HR 0.89, p=0.07) 13. Both studies compared different groups of children and thus attempted to control for relevant child-level confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second study, Marcus et al assessed injury risk among stimulant-treated children over a single treatment period of at least 4 months. Children who were more adherent to medication were less likely to experience an injury than children who were less adherent (injuries/person-year: 0.227; 95% CI 0.214 to 0.240 vs 0.230; 95% CI 0.204 to 0.254; adjusted HR 0.89, p=0.07) 13. Both studies compared different groups of children and thus attempted to control for relevant child-level confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Observational study results evaluating injury rates showed that use of long-acting MPH was associated with a lower odds of injury compared with use of standard formulation MPH 12. In addition, injury rates were slightly lower among adherent stimulant users compared with children who were less adherent 13. Although the latter two studies suggest that overall exposure to stimulant medication use may be protective for injuries, residual confounding may have resulted from uncontrolled between-group factors associated with stimulant use and injury events, such as parental supervision and health care seeking behaviour.…”
Section: Introductionmentioning
confidence: 98%
“…They find that Ritalin use significantly worsened emotional functioning for girls and academic outcomes for boys. Regarding accumulation of health capital, we are aware of only one study by Marcus et al (2008) that considers the link between pharmacological treatment and health. Their study uses a duration model to investigate the association between compliance in pharmacological treatment and injuries for a group of children in treatment.…”
Section: (2009)mentioning
confidence: 99%
“…Epidemiologic data suggest that children diagnosed with attention-deficit/ hyperactivity disorder-combined type (ADHD-C) have higher pedestrian injury rates when compared with typically developing peers, 2,3 as well as when compared with children with other developmental disabilities. 4,5 Although there is growing consensus of a link between ADHD-C and pediatric injury risk, [6][7][8][9] and between ADHD-C and pedestrian injury risk, 10 the causal processes underlying this link remain unclear. 11,12 Crossing streets safely requires simultaneous engagement in several cognitive and perceptual tasks that may prove difficult for children with ADHD-C because of their deficits in attention, difficulty with selfregulation, and common comorbid symptomatology, such as oppositional behavior problems.…”
mentioning
confidence: 99%